(untitled) (American Journal of Islam and Society, 1989)
More than four hundred scholars and guests from around the world attended the "Second International Islamic Conference on Prevention of Drugs and Alcohol" held at the International Islamic University, Islamabad, Pakistan Shawwal 26-28 1409/June 1-3, 1989. The conference, sponsored by Rabita al-Alam al-Islami, Makkah alMukarramah (World Muslim League), and the IIU in Islamabad, re-affim1ed the commitment of the Muslim Ummah to elirnfoate the threat and menace of drugs and alcohol in Islamic states and societies world-wide. Scholars attending the conference represented both the natural and social sciences, and individual professions ranged from medical doctors and law enforcement authorities to social engineers and Islamic authorities in Seerah and Shariah. More than 70 scholars presented papers on critical aspects of the problem. The conference agenda embraced six major concerns: l) The Nature and Extent of Drug Abuse. 2) Biological Mechanism. 3) Religious and Educational Outlook. 4 ) Social Context of Drug Abuse ...